Efficient extraction of bioactive flavonoids from Celtis sinensis leaves using deep eutectic solvent as green media. Issue 29 (18th May 2021) - Wang, Lei; Fang, Xianying; Hu, Yang; Zhang, Yiwei; Qi, Zhipeng; Li, Jie; Zhao, Linguo
Abstract : In recent years, deep eutectic solvent (DES) has attracted comprehensive attention on the extraction of natural products, and is regarded as an alternative to traditional organic solvents for the environmental advantages. Abstract : In recent years, deep eutectic solvent (DES) has attracted comprehensive attention on the extraction of natural products, and is regarded as an alternative to traditional organic solvents for the environmental advantages. Twenty-six DESs were compared for their extraction yield of total flavonoids and isovitexin (the main flavonoid in Celtis sinensis ) from Celtis sinensis . The results show that the extraction yields of total flavonoids by betaine/glycolic acid (DES8), ethylamine hydrochloride/1, 2-propanediol (DES12) and tetrapropylammonium bromide/lactic acid (DES17) are the highest, while the extraction yields of isovitexin by ethylene glycol/malonic acid (DES23), ethylene glycol/glycolic acid (DES24) and 1, 2-propanediol/glycolic acid (DES26) are the highest. The extraction conditions using the above six DESs were further optimized systematically. Under optimum conditions, the extraction rates of total flavonoids and isovitexin can be increased up to 95.39 and 10.58 mg g −1, respectively, which were significantly higher than that of methanol extraction. In order to exclude the effect of DESs on the bioactivity of Celtis sinensis extract, the macroporous resin D-101 was used to purify the total flavonoids from DESs extract, and the recovery rates of flavonoids from the above six kinds of DESs were all over 80%. Next, the anti-inflammatory activity of DES extracts was compared using a lymphocyte transformation experiment. The result showed that the inhibition rate of the DES24 extract on the proliferation of Con A-activated T cells was up to 72% with an IC50 value of 124.8 μg mL −1 . None of the DESs extracted exhibited cytotoxicity on normal T cells. The mechanism of the anti-inflammatory activity against Con A-activated T cells may be that DES24 flavonoids extract induced the apoptosis of inflammatory T cells, and activated the expression of pro-apoptotic protein. Taken together, DES has showed significant advantages on the extraction of natural products for the relatively mild extraction condition, high yield and environmental-friendliness.